Gestión por procesos y la cadena de valor en la industria farmacéutica - Flemming Abad, César Germán (2019)
Since 2015, an analysis and development work has been carried out in which scientific leaders, clinical researchers, research managers and managers from both the public and private sectors have participated, aimed at implementing a new line of business in the Laboratories G and F Farma, involving the main Stakeholders in the Peruvian pharmaceutical industry in which they actively participated with the managerial leaders in charge representing the various areas in marketing and production, in the public and private pharmaceutical sector. During the development of the project, the need for medicines that are not available in the Peruvian market and that had become a barrier to the development of other lines of work was identified; as well as the need to implement Industrial Engineering tools that were not used in the daily style of work that had been done in the analyzed company, having become a great limitation. With this objective, the Hospital Strategic Products (PEH) line was established, which initially (with a predecessor line) addressed products related to specialties such as oncohematological, oncological, endocrinological and later development. He identified other specialties and needs in both sectors, in the specialty of Orphan and Rare Diseases (EHR).